Chemical characterization and breadmaking potential of spelt versus wheat flour. (January 2018) - Frakolaki, Georgia; Giannou, Virginia; Topakas, Evangelos; Tzia, Constantina
Abstract: Spelt flour has become increasingly popular due to its superior nutritional properties. Aim of this work was to conduct a comparative evaluation of the chemical composition of wheat and spelt flour, their dough rheology and breadmaking properties. Flours' comparison included the determination of their moisture, ash, protein, gluten, gliadin, glutenin, starch and total carbohydrates content. Their rheological properties were also analyzed through farinograph and extensiograph. The protein fractions of the two flours were evaluated by electrophoresis. Finally, each flour was separately used for breadmaking and the characteristics of the resulting bakery products (specific volume, dough swelling, crust and crumb color, hardness and water activity), were evaluated. Although spelt flour has higher protein content, it contains less gluten, while wheat flour provides a stronger and more elastic dough with superior breadmaking properties. Bread from spelt flour exhibits lower specific volume, darker crumb and crust color and increased crust and crumb hardness. Highlights: Chemical composition, dough rheology and breadmaking potential of wheat and spelt flour are compared. Spelt flour has higher protein content but less gluten than wheat flour. Wheat dough is stronger and more elastic and has superior breadmaking potential. Spelt samples have lower specific volume and less appealing sensory characteristics. Breadmaking potential of spelt flour can be enhanced if combined with wheat flour.